Identifikasi dan Karakterisasi Mikroba pada Tape Singkong (Manihot esculenta) Setelah Pengisolasian melalui Teknik Pengecatan - Annisa Tuzzahra; Ardi Mustakim (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Cassava tape is a traditional fermented product widely consumed in Indonesia, especially in rural areas. It is produced from cassava (Manihot esculenta) through the activity of microorganisms during the fermentation process. The presence of microbes in this process plays a crucial role in the flavor, aroma, texture, and final quality of the product. The microorganisms involved, including bacteria, molds, and yeasts, work synergistically to break down the carbohydrate components of cassava into simpler products, resulting in the sweet taste and distinctive aroma of tape. This study aimed to identify and characterize the microbes present in cassava tape through isolation and microscopic staining using safranin. The isolation process involved several stages: sequential sample dilution, inoculation onto Nutrient Agar (NA) media using the pour method, and incubation at 37°C for 24 hours. The growing microbial colonies were observed macroscopically, then collected and subjected to simple safranin staining to determine the shape and distribution pattern of the microbial cells microscopically. Observations revealed colonies with diverse morphologies, including rod-shaped (bacilli) and spherical (cocci), evenly distributed across the observation area. This indicates that cassava tape contains microorganisms of various morphologies that play a role in the fermentation process. Simple safranin staining has been shown to provide an initial overview of the presence and form of microbes, although further identification to the genus or species level requires further tests such as Gram staining, biochemical tests, and molecular analysis. These findings open up opportunities for further in-depth research into consumption safety, the functional role of microbes in tape fermentation, and its potential use as a source of natural probiotics in traditional fermented foods.